Exploring Teachers’ Challenges and Strategies Teaching English Speaking Skills in Religious Bilingual High Schools - Masumah, Fithriyatul; Alief Noor Farida (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study investigates how English teachers navigate the complexities of developing students’ speaking proficiency in bilingual classes within a religious senior high school context. Using a qualitative case study approach, data were collected through semi-structured interview, classroom observations, and document analysis to obtain an in-depth understanding of teachers’ strategies and challenges. The findings reveal that teachers employ effective, cognitive, and technological strategies to foster students’ confidence in speaking English. However, they have persistent challenges including constraint time, language barriers, low motivation and confidence, and classroom dynamics. The study also highlights how teachers overcome the challenges by integrating song and technology, providing explicit scaffolding, and creating a psychologically safe environment. These findings emphasize the need for professional development programs that can address challenges and integrate innovative teaching approaches.